THE EFFECT OF DIVERSIFICATION ON PERFORMANCE AND RISK (Case on Shariah Bank in Indonesia Period 2019-2020) - Shinta Qurrota Aini; Estu Widarwati; Nunik Nurmalasari; E Wityasminigsih (STIESA Press, 2023)
Banks has been able to increase its capability by diversified their services and invesment hat implicate increasing their credit risk, market risk, operational risk, liquidity risk, legal risk, strategic, compliance risk, and reputation risk. This study aims to examine the impact of diversification on the bank performance which risk as moderation variable. Samples used are 10 sharia banks listed in Authority Indonesian Authority Service (OJK) during 2019-2020. Income diversification as proxy bank diversification, bank performance measured by Return on Equity (ROE), and Z-score used to measure the bank risk. The results showed there is no significant impact of diversification on the bank performance and bank risk. Anyway, bank should keep the quality in good condition for improving the performance and minimizing the risk based on macro factor consideration such abnormal economic affected pandemic.